Transforming Growth Factor Beta Signaling in Dendritic Cells Is Required for Immunotolerance to Sperm in the Epididymis - Pierucci-Alves, Fernando; Midura-Kiela, Monica T.; Fleming, Sherry D.; Schultz, Bruce D.; Kiela, Pawel R. (Frontiers in Immunology, 2018)
The epididymis exhibits a less restrictive physical blood-tissue barrier than the testis and, while numerous immunosuppressive factors have been identified in the latter, no mechanisms for epididymal immunotolerance have been identified to date. Therefore, data are currently insufficient to explain how the immune system tolerates the extremely large load of novel antigens expressed on sperm, which become present in the male body after puberty, i.e. long after central tolerance was established. This study tested the hypothesis that TGFβ-signaling in dendritic cells (DCs) is required for immunotolerance to sperm located in the epididymis, and that male mice lacking TGFβ-signaling in DCs would develop severe epididymal inflammation. To test this, we employed adult Tgfbr2ΔDC males, which exhibit a significant reduction of Tgfbr2 expression and TGFβ-signaling in DCs, as reported previously. Results show that Tgfbr2ΔDC males exhibit sperm-specific immune response and severe epididymal leukocytosis. This phenotype is consistent with epididymal loss of immunotolerance to sperm, and suggests that TGFβ-signaling in DCs is a factor required for a non-inflammatory steady state in the epididymis, and therefore for male tract homeostasis and function.